Study on the gallery structure cracking mechanisms and cracking control in dam construction site. (March 2021) - Lin, Peng; Ning, Zeyu; Shi, Jie; Liu, Chang; Chen, Wenfu; Tan, Yaosheng
Highlights: Gallery concrete, together with foundation and environment are fully investigated. The distribution of the wind speed inside the gallery of the dam is revealed. Cracking risk map is drawn based on the analysis of the cracking mechanisms. An engineering procedure is proposed to prevent the gallery cracking. Abstract: Gallery cracking often occurs during the construction and operation periods of dams. It is very important to implement cracking control measures through the whole dam design, construction, and management process. In this study, a case study is conducted to investigate the gallery cracking mechanisms, risks, and controls of a super-high arch dam during the construction period. By employing 3D finite element methods (FEM), 3D computational fluid dynamics (CFD), and site monitoring, the cracking risks and mechanisms of the gallery are studied relating to different factors of the material properties, structure design, foundation settlement, and environment. The results show that the stress concentration due to the complex geometry and the air temperature drop is the main structural factor and environmental factor, respectively. The wind will spread and reach an extreme speed at the intersection of the gallery if the entrance is not closed, which may accelerate the air temperature drop and the humidity loss at the surface of the gallery. Based on the cracking mechanism analysis and the risk control investigation, a set of engineering procedures is proposed to control and prevent the gallery cracking through optimizing the design theory, the construction methods, and the management philosophy. The application results in the further construction of the super-high arch dam verify the effectiveness of the engineering procedure in the cracking control of similar galleries.